THE STUDY OF STITCH PARAMETERS ON THE EFFECT OF STITCH STRENGTH OF THE POLYESTER LINING FABRICS - (:unkn) unknown (EGE UNIVERSITESI, 2011)
Lining fabrics are the fabrics hiding seams by covering some parts or all parts of inside of clothes, and having weight, tenacity, colour, movement ability, touch suitable to the type of superior fabric. In this study, it was aimed to determine the correct sewing conditions for good seam strength after the observation of the parameters of 100% polyester lining fabric's resistance to the forces while using. In this respect, fabric course, sewing yam, sewing needle, stitch pace's effects on the seam strength, seam elongation and seam efficiency was observed. Eight different seam yams, two different sizes sewing needle, two different seam density and three different fabric course were used while sewing the fabric. Test results were analysed by using the SPSS statistical software programme. At the end of the studies, the highest seam strength and elongation values obtained in the diagonal way of fabric, more than the warp direction, parallel to the fabric tensile strength results. Also it was observed that as the yam thickness and seam density increase, the seam strength also increases.
Keywords: Lining fabric; Sewing strength; Seam direction; Sewing parameters; Seam density